Analysis of Customer’s Religiosity, Product Knowledge, and Their Intention to Use Micro Financing Program (MFP) Based on Mudharabah Scheme - Waluyo, Bambang; Rozza, Sylvia; ‎ , Abdillah; Dwie Oktavia, Fadya; Dwi Novita, Amanda (KnE Social Sciences, 2024)
Brayan Bumi Banyumas Joint Village-Owned Enterprise (BUMDESMA) has been running a conventional financial business through lending to its customers. However, BUMDESMA also has the opportunity to market Islamic finance-based products, namely profit sharing with a mudharabah contract through the micro financing program (MFP). This research aims to measure and explore the religiosity of BUMDESMA customers as potential partners and their understanding of MFP based on mudharabah scheme to see their intention to use it. In this qualitative research, data were collected by interviewing 103 SME business owners in Banyumas as BUMDESMA’s prospective customers. The results showed that in terms of religiosity, people understand that in any business they should not commit deceptive actions, obey what has been agreed in the contract, and pay off debts even by selling other assets owned. It means that they have basic religiosity in this matter. Likewise, in terms of understanding MFP, the potential partners know that in a profit-sharing-based product with a mudharabah contract, their position is as a business actor who acts as a fund manager who must manage funds and run the business well, to generate profits. They are interested in becoming customers when the MFP is launched. The research implies that it becomes a reference for BUMDESMA which will offer MFP products, there are already potential partners who have good religiosity, understand the product, and are interested in becoming partners or customers. Keywords: village-owned enterprise, micro financing program (MFP), customer’s religiosity, product knowledge, interest